Legal Uncertainty on the Obligations of People Who Hear, See or Know the Occurrence of Domestic Violence Crimes - Bambang Tri Bawono; Andri Winjaya Laksana; Moh. Nurul Huda (UNISSULA Semarang, 2026)
One of the problems that until now is still mushrooming in Indonesia is related to violence in the stairs. The problem of domestic violence regulation is related to the existence of legal uncertainty for the community or everyone who hears, sees, or knows the occurrence of a crime of domestic violence is obliged to prevent, protect the law and provide emergency assistance to the victim and assist in the process of submitting an application for the determination of protection. The type of research used in this study uses empirical legal research, using a descriptive research type which will later be analyzed using qualitative analysis. The results of the study show that there is legal uncertainty in article 15 of the PKDRT Law. This is because the article contains the phrase mandatory, while it is not accompanied by sanctions, while in point 268 of Attachment 1 of the Law on the Formation of Legislation it expressly says that When there is a mandatory word, sanctions must be given for those who do not do it.